Physical performance and biological maturity of primary school children - Gulbiani, Tristan; Dvali, Manuchar (Modern Issues of Medicine and Management, 2025)
The results of one-factor variance analysis indicate the necessity of incorporating into the physical training of primary school children methods and tools aimed at improving the efficiency of aerobic energy production, as an integral part of the internal structure of children's preparedness for strenuous muscular activity. Factor analysis revealed that the aerobic abilities of primary school children have a heterogeneous structure and are largely determined by capacity, power, the feasibility of potential aerobic power, and aerobic efficiency.